780 IMPROVING NUTRITIONAL SUPPORT FOR POST-SURGICAL FEMUR FRACTURE PATIENTS AT ST MARY'S HOSPITAL, LONDON. (8th March 2022) - Donnelly, L; Sharpe, S; Heber, I; Morgan, C
Abstract: Introduction: Malnutrition represents a common complication in femur fracture patients and is primarily caused by poor dietary intake. Malnutrition is associated with poor clinical outcomes, and is the strongest independent risk factor for recurrent femur fracture. High protein oral nutrition supplements (ONS) have been associated with improved clinical outcomes after femur fracture, including reduced complications, length of hospital stay, mortality and bone mineral density loss, and increases in functional status and quality of life (Volkert, Beck, Cederholm et al., Clinical Nutrition, 38, 10–47)). Accordingly, the European Society for Clinical Nutrition and Metabolism (ESPEN) advocates the use of ONS with all femur fracture patients in hospital. Aim To improve nutritional support for post-surgical femur fracture patients at St Mary's Hospital, London. Methods: We plan to carry out three PDSA cycles to evaluate whether two separate interventions are effective in increasing the prescription rate of ONS in post-surgical femur patients. Each PDSA cycle included all patients who underwent surgical treatment for femur fracture during a one month period. Results: 'Cycle 1' included 18 patients (mean age: 84.6 years; range: 68–98 years) treated in March 2021. ONS were prescribed in 11% (2/18) post-surgical femur fracture patients. 'Intervention 1' comprised a dietician-led presentation during the Geriatric department weekly teaching session on 17/05/21. 'Cycle 2' data will be collected one month after 'Intervention 1'. Conclusion: 'Cycle 1' results revealed low rates of ONS prescriptions for post-surgical femur patients. We anticipate higher ONS prescription rates following 'Intervention 1'. We believe that doctors' and dieticians' awareness of the importance of nutritional support for post-surgical femur fracture patients is key to the success of this quality improvement project.